Integrating the case method approach in 21st century teaching: Empowering the development of effective and innovative teaching instruments - Dewi, Nora Ronita; Hartoyo, Indra; Natalia, Christine Helena (UNIB Press, 2024)
This study investigated how combining the case method approach and technology tools can be effective in 21st-century instructional methods. The case method approach in teaching instruments focuses on assisting students develop critical thinking, problem-solving, and communication skills. Its goal is to provide practical learning experiences that allow students to apply these skills in real-world situations. Teachers can successfully incorporate the case method approach into their instrument teaching by selecting appropriate case studies, establishing clear learning objectives, designing engaging activities,and incorporating technology tools such as digital media, interactive simulations, and online platforms. The study findings indicate that integrating the case method approach in technology tools in instruction, course syllabus, and materials improved student engagement and access to information, encouraged student collaboration and communication, and improved critical thinking, problem-solving, and communication skills. As a result, incorporating the case method approach and technology tools into teaching instruments allows teachers to provide a hands-on learning experience that focuses on essential skills. This integration creates a dynamic and interactive learning environment, promoting skill development and optimizing students' overall learning experience.